Perbandingan Tingkat Motivasi Belajar pada Siswa Kelas VII yang Menggunakan dan Tidak Menggunakan Media Audio Visual pada Pembelajaran Tarikh - Nurrohman, Rouf Zidan; Ru'iya, Sutipyo (Samodra Ilmu: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2024)
The background of the problem in this study is the importance of learning motivation for students. One way to increase learning motivation is to involve audio-visual media in learning. It is expected that the use of audio-visual media in the learning process can create a pleasant atmosphere, especially during datum learning. This study attempts to compare students' learning motivation in classes that use audio-visual media and without using audio-visual media. The study was conducted at SMP Muhammadiyah 9 Yogyakarta, in class VII C as an experimental class (which uses audio-visual media) and class VII D as a control class (which does not use audio-visual). The data analysis method used is the Mann-Whitney test with the help of the SPSS Version 25 application. The results of this study indicate that the level of learning motivation between the experimental class that uses audio-visual media in learning dates is included in the moderate category with 16 students with a percentage of 61.54% and the control class that does not use audio-visual media in learning dates is included in the moderate category with 15 students with a percentage of 57.69%. Then based on the hypothesis test using the Mann-Whitney test shows the asypmp value. sig. (2-tailed) of 0.469 > 0.05. So in this study it is stated that there is no significant difference in learning motivation between the experimental class and the control class in Tarikh learning.